Rubin H. Flocks and Colloidal Gold Treatments for Prostate Cancer - Henry M. Rosevear; Andrew J. Lightfoot; Michael A. O'Donnell; Charles E. Platz; Stefan A. Loening; Charles E. Hawtrey (The Scientific World Journal)
In the early 1950s, Rubin H. Flocks of the University of Iowa began to treat prostate cancer patients with colloidal gold (Au198) therapy, evolving his technique over nearly 25 years in 1515 patients. We reviewed the long-term outcomes of Flocks' prostate cancer patients as compared to those patients treated by other methods at the University of Iowa before Flocks' chairmanship. We reviewed archived patient records, Flocks' published data, and long-term survival data from the Iowa Tumor Registry to determine short- and long-term outcomes of Flocks' work with colloidal gold. We also reviewed the literature of Flocks' time to compare his outcomes against those of his contemporaries. The use of colloidal gold, either as primary or adjunctive therapy, provided short- and long-term survival benefit for the majority of Flocks' patients as compared to historical treatment options (p < 0.001). Flocks' use of colloidal gold for the treatment of locally advanced prostate cancer offered short- and long-term survival benefits compared to other contemporary treatments.